Channels of published research communication used by Malaysian authors in computer science and information technology - Gu, Y.; Zainab, Awang Ngah (Department of Library & Information Science, Faculty of Computer Science and Information Technology, University of Malaya, 2000)
Analyse 389 records retrieved from Inspec (1990-1999), Compendex (1987-1999) and IEL (IEE/IEEE Electronic library)(1987-1999). The records comprised 159 journal articles, 229 conference papers and 1 monograph chapter. The subject coverage was computer science and information technology. The yearly output of Malaysian publications indicated a gentle upward trend. The highest contributions was 87 published in 1997. The channels used to publish differ slightly from the norm for scientists. Conference papers were preferred to journal articles. The spread of conference papers used to publish indicate three zonal distributions; the nucleus, moderate and low productivity in the ratio of 19 : 41 : 88, leading to a clustering index of 2.15. This shows that Malaysian conference contributions were concentrated in a few proceedings. No clear core journals can be identified for the journal articles and contributions were distributed in a wide variety of journal titles. Malaysian Journal of Computer Science published the highest number of journal articles. More than 83 of the articles were published in journals from the UK, USA, the Netherlands and Malaysia.